Can the Yield Spread predict economic growth? An assessment for European countries - Moura, Rubens Guimarães Togeiro de (2015)
Double Degree. A Work Project presented as part of the requirements for the Award of a Masters Degree in Economics from the NOVA- School of Business and Economics and a Masters Degree in Management from Louvain School of Management